Analysis of Internal Inventory Control Systems and Accounting Information Systems For Product Stock Inventory in A National Corporate Wear Manufacturing Company - Pramudito, Dendy K; Kamar, Karnawi; Bakri, Asri Ady; Husaini; Pratiwi, Noor Komari (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to evaluate the impact of the accounting information system and internal control system on goods inventory. This kind of study employs a descriptive-qualitative methodology. Field research is the method used in this study. The qualitative descriptive analysis method of data analysis was applied in this study. According to the study's findings, the control environment that was put in place proved to be successful because, with a 50% score, three out of the six control environment indicators satisfied the standards for the control environment. The risk assessment implemented has been very effective, with a score of 100% for three of the three indicators that fulfill the risk assessment requirements. The control activities implemented have been effective, with a score of 60% for three of five indicators that fulfill the control activity requirements. The information and communication implemented are very effective, with a score of 100%. The monitoring carried out has been very effective. The accounting information system implemented is very effective, with a score of 100%. Using the COSO Framework to set up an internal control system and an accounting information system has not yet fully met the requirements; the results from the checklist form show that more than 80% of the items are suitable.